Comparison of living-donor lobar lung transplantation and cadaveric lung transplantation for pulmonary hypertension. (1st February 2023) - Kayawake, Hidenao; Tanaka, Satona; Yamada, Yoshito; Baba, Shiro; Kinoshita, Hideyuki; Yamazaki, Kazuhiro; Ikeda, Tadashi; Minatoya, Kenji; Yutaka, Yojiro; Hamaji, Masatsugu; Ohsumi, Akihiro; Nakajima, Daisuke; et al.
Graphical abstract: Abstract: OBJECTIVES: Living-donor lobar lung transplantation (LDLLT) is a life-saving procedure for critically ill patients with various lung diseases, including pulmonary hypertension (PH). However, there are concerns regarding the development of heart failure with pulmonary oedema after LDLLT in which only 1 or 2 lobes are implanted. This study aimed to compare the preoperative conditions and postoperative outcomes of LDLLT with those of cadaveric lung transplantation (CLT) in PH patients. METHODS: Between 2008 and 2021, 34 lung transplants for PH, including 12 LDLLTs (5 single and 7 bilateral) and 22 bilateral CLTs, were performed. Preoperative variables and postoperative outcomes were retrospectively compared between the 2 procedures. RESULTS: Based on the preoperative variables of less ambulatory ability (41.7% vs 100%, P < 0.001), a higher proportion of World Health Organization class 4 (83.3% vs 18.2%, P < 0.001) and higher mean pulmonary artery pressure (74.4 vs 57.3 mmHg, P = 0.040), LDLLT patients were more debilitated than CLT patients. Nevertheless, hospital death was similar between the 2 groups (8.3% vs 9.1%, P > 0.99, respectively). Furthermore, the 5-year overall survival rate was similar between the 2 groups (90.0% vs 76.3%, P = 0.489). CONCLUSIONS: Although LDLLT patients with PH had worse preoperative conditions and received smaller grafts than CLT patients, LDLLT patients demonstrated similar perioperative outcomes and prognoses as CLT patients. LDLLT is a viable treatment option for patients with PH. Abstract : Lung transplantation (LTx) has been performed as the final option for saving the lives of patients with end-stage pulmonary diseases with satisfactory outcomes, and the number of LTx procedures performed has been gradually increasing [1].